Fungsi Tradisi Nyadran di Desa Bumi Arum Majasto: Teori William. R. Bascom - Pitaloka, Diana (DIWANGKARA: Jurnal Pendidikan, Bahasa, Sastra dan Budaya Jawa, 2024)
Tradition is an action or deed that is carried out continuously by a person or group that is considered beneficial. Traditions are old and come from ancestors (Simanjuntak, BA: 2016). The tradition of "Sandranan" in the village of Bumi Arum Majasto is one of the oral literature that is still believed by the local community and has become a tradition for generations to send prayers to the ancestors and to commemorate the services of the elders or founder of the village of Bumi Arum Majasto, namely Ki Ageng Sutowijaya. The purpose of this study is to describe the function of the tradition that resides in Bumi Arum Majasto by using William R. Bascom's theory. In William R. Bascom's theory, the function of the nation of literature is (1) a form of entertainment, (2) a means of validating cultural institutions and institutions, (3) education, (4) a coercive or supervisory tool so that norms are still obeyed. The benefits of this research are expected to increase knowledge and experience.